The Influence of Organizational Culture and Career Development on the Motivation of Civil Servants in the General Section of the Regional Secretariat of Ketapang Regency - Nadya Adriani Pardede; Irfan Mahdi (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to analyze the influence of organizational culture and career development on the motivation of Civil Servants working in the General Section of the Regional Secretariat of Ketapang Regency. The research approach uses a quantitative method with an associative design. The research sample consists of all 37 Civil Servants in the General Section, determined using a saturated sampling technique. Primary data were collected through interviews and questionnaires, while secondary data were obtained from staffing documents related to discipline, performance, training, and promotion. Data analysis includes instrument testing, classical assumption testing, and multiple linear regression. The results of the study show that organizational culture has a positive and significant influence on motivation, and career development is also proven to have a positive and significant influence on motivation. Simultaneously, both variables contribute 44.2 percent to the variation in employee motivation. This study emphasizes the importance of the quality of organizational culture and the clarity of career pathways in encouraging the motivation of public sector employees. Its practical implications include the need for structuring work culture development, equal distribution of training opportunities, and a more transparent promotion mechanism. Future studies may include other variables such as leadership, compensation, or workload so that employee motivation can be understood more comprehensively.